Structural study and thermal stability of Artemetin extracted from Artemisia absinthium L - Hbika, Asmae; Bouyanzer, Abdelhamid; Saadi, Mohamed; Ammari, Lahcen El; Benali, Mohammed; Majidi, Lhou; Gharibi, El Khadir; Zarrouk, Abdelkader (Chemical Data Collections, 2022)
The interest given to the bioactive properties of phenolic compounds, extracted from aromatic and medicinal plants, has eclipsed in a sense the physicochemical characterization of these molecules which are from a chemical point of view only chemical reagents. In this work, the molecule C20H20O8 (Artemetin), extracted from Artemisia absinthium L by hexane and then by diethyl ether was studied. The Artemetin extract was concentrated and characterized by High-performance liquid chromatography-Diode array detector, Single crystals and powder were isolated by solvent evaporation and recrystallization. They were characterized by X-Ray Diffraction, Infrared spectroscopy, Ultraviolet–visible spectroscopy, scanning electron microscope- Energy-dispersive X-ray spectroscopy, Differential Thermal-Thermogravimetric-Calorimetry Analysis. The concentrate of the extract can reach 98% in Artemetin. The structure of the isolated single crystal is identical to that of Artemetin with more precision in the interatomic distances and angles. The thermal stability range of artemetin was studied in an oxidizing (air) or inert (N2) atmosphere. The temperature and enthalpy of fusion were determined (Tfus = 160 °C, ΔHfus = 1.36 kJ/mol). Quantum chemical calculations have made it possible to evaluate the optimized geometry of artemetin, which is described as a soft molecule with a high molecular polarity that can give it a high chemical reactivity.